(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Unconventional spaces used for performance and theater have been increasingly appropriated by contemporary directors, mainly due to the spatial qualities with which the current scenic dynamics involves performers and participants, generally called site-specific. Based on the theories of Carlson (1989, 2012), Rufford (2015) and Pearson (2001), this article discusses occupations of different spatial configurations, whether in industrial warehouses, in public or semi-public spaces in the city that ensure a participatory relationship between stage and audience and establish a relevant role in fruition between body and space, performed outside the theater building.